Influence of determining factors on the distribution and ecological niche of honeybees (Hymenoptera: Apidae) in Ibarra, Ecuador - Jácome Aguirre, Gabriel Alexis; Huera Ipial, Jenifer Dayana; López Gómez, Andrea Luciana; Arias Muñoz , Darío Paúl; Aguirre Caicedo, Ritha Alexandra del Pilar; Rosales Enríquez , Oscar (SATHIRI, 2025)
Apis mellifera L. is a species of vital importance as pollinator, whose presence is fundamental for the proper development of ecosystems. However, various anthropogenic factors cause alterations in its ecological niche. This research analyzes the presence of Apis mellifera along with bioclimatic, environmental, and agricultural variables using the maximum entropy model (MaxEnt) to determine the niche and potential distribution of the species within the study area. As a result, it was determined that the ecological niche of honeybees is mainly determined by factors such as the type of vegetation cover, honey production, and the annual range of temperature (Bio7), identifying areas with high suitability covering a total of 645.99 hectares corresponding to grasslands and crops, especially in the San Antonio de Ibarra parish. The model was validated using the AUC (0.904) and TSS (0.618) values. Certainly, it is evident that Apis mellifera finds its ideal habitat in small and specific areas where it would be feasible to promote the development of beekeeping.